2004
DOI: 10.1128/jb.186.10.2973-2983.2004
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the MexAB-OprM Multidrug Efflux System of Pseudomonas aeruginosa : Identification and Characterization of Mutations in mexA Compromising MexA Multimerization and Interaction with MexB

Abstract: The membrane fusion protein (MFP) component, MexA, of the MexAB-OprM multidrug efflux system of P. aeruginosa is proposed to link the inner (MexB) and outer (OprM) membrane components of this pump as a probable oligomer. A cross-linking approach confirmed the in vivo interaction of MexA and MexB, while a LexA-based assay for assessing protein-protein interaction similarly confirmed MexA multimerization. Mutations compromising the MexA contribution to antibiotic resistance but yielding wild-type levels of MexA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 87 publications
0
79
0
Order By: Relevance
“…Crystal structures of the MFP MexA reveal an elongated monomer with an extended ␣-helical coiled-coil domain and two globular domains consisting primarily of ␤-strands (2,199). Substantial biochemical evidence suggests that MFPs exist as oligomers (329,334,549), and in crystals, MexA protomers oligomerize in spirals, forming the basis for the model in Fig. 14 (blue section).…”
Section: Protein Trafficking Between and Across Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystal structures of the MFP MexA reveal an elongated monomer with an extended ␣-helical coiled-coil domain and two globular domains consisting primarily of ␤-strands (2,199). Substantial biochemical evidence suggests that MFPs exist as oligomers (329,334,549), and in crystals, MexA protomers oligomerize in spirals, forming the basis for the model in Fig. 14 (blue section).…”
Section: Protein Trafficking Between and Across Membranesmentioning
confidence: 99%
“…In contrast to earlier predictions that suggested that MFPs might span the periplasm with their N and C termini bound to the inner and outer membranes, respectively (548), the structures suggest that both the N and C termini are likely to lie in close proximity to the inner membrane. Mutagenesis and suppressor analyses suggest that the C termini of the MFPs interact with the inner membrane transporters (at least in the case of the RND transporters Mex and Acr) (139,329,330), while the N terminus may be involved in oligomerization of the MFPs (329).…”
Section: Protein Trafficking Between and Across Membranesmentioning
confidence: 99%
“…The bacterial strains and plasmids used in this study are listed in Table 1. Routine growth of P. aeruginosa and Escherichia coli was carried out in Luria broth (LB) as before (52), with antibiotic supplementation to maintain plasmids as needed (for pUC18, ampicillin [100 g/ml]; for mini-CTX-lacZ and its derivatives, tetracycline [10 g/ml for E. coli and 75 to 100 g/ml for P. aeruginosa]; for pK18mobsacB and its derivatives, kanamycin [50 g/ml]; for pFLP2, ampicillin [100 g/ml for E. coli] or carbenicillin [150 g/ml for P. aeruginosa]; and for pMMB207 and its derivatives, chloramphenicol [10 g/ml for E. coli and 75 to 100 g/ml for P. aeruginosa]). Fe-limited BM2 succinate and BM2 glucose minimal media have been described previously (61) and were supplemented with FeCl 3 as and where indicated.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial strains and plasmids used in this study are listed in Table 1. Bacteria were cultivated at 37 uC in Luria (L) broth as before (Nehme et al, 2004) supplemented with antibiotics to maintain plasmids as needed [pEX18Tc, pRK415 and their derivatives: tetracycline (10 mg ml 21 , E. coli; 75 mg ml 21 , P. aeruginosa); pK18MobSacB and its derivatives: kanamycin (50 mg ml 21 , E. coli; 1500 mg ml 21 , P. aeruginosa); pUCP18 and its derivatives: ampicillin (100 mg ml 21 , E. coli) or carbenicillin (800 mg ml 21 , P. aeruginosa); pUT : : mini-Tn5-tet: tetracycline (10 mg ml 21 , E. coli); pCR-Blunt II-TOPO: ampicillin (100 mg ml 21 , E. coli)]. The iron-limited succinate minimal media [here dubbed 'A' (Meyer & Abdallah, 1978) and 'B' (Poole et al, 1990)] have been described previously.…”
Section: Methodsmentioning
confidence: 99%